5-Hydroxy polymethoxyflavones inhibit glycosaminoglycan biosynthesis in lung and colon cancer cells. (March 2017) - Qiu, Peiju; Cui, Yidi; Xiao, Hang; Han, Zhangrun; Ma, He; Tang, Yang; Xu, Huixin; Zhang, Lijuan
Abstract: 5-hydroxy-3, 6, 7, 8, 3′, 4′-hexamethoxyflavone (5HHMF) and 5-hydroxy-6, 7, 8, 3′, 4′-pentamethoxyflavone (5HPMF) are the predominant polymethoxyflavones in orange peel. Here, we showed how 5HHMF or 5HPMF modulated the amount of pre-existing and newly synthesized glycosaminoglycans (GAG) in lung and colon cancer cells. 5HPMF treatment disrupted the formation of FGF/FGFR1c/GAG ternary signaling complex in cell surface. Moreover, 5HHMF remarkably decreased the content of nonsulfated and 3- or 6-sulfated disaccharides of heparan sulfate while no significant changes occurred in that of chondroitin sulfate detected by 1-phenyl-3-methyl-5-pyrazolone (PMP) isotope labeling plus LC/MS analysis. Furthermore, quantification of metabolic incorporating 34 S isotope-labeled sulfate into GAG of cultured cells indicated that 5HHMF decreased the sulfated disaccharides of the newly synthesized GAGs by 54%. Overall, the results indicated that 5HHMF and 5HPMF were potential inhibitors of GAG biosynthesis. Our results indicated that GAGs might be the long sought signaling molecules affected by 5HHMF and 5HPMF that lead to lung and colon cancer cell death.